PERTANGGUNGJAWABAN ORANGTUA KANDUNG DALAM KASUS KECELAKAAN LALU LINTAS YANG DIALAMI OLEH ANAK SEBAGAI TERSANGKA DI WILAYAH HUKUM POLRES SLEMAN - Rachmad Wijayanto; Francisca Romana Harjiyatni; Hartanti Hartanti (Universitas Janabadra, 2018)
This study aims to analyze the implementation of criminal liability by parents as a result of traffic accidents experienced by children in the area of Polres Sleman and criminal alternative in order to be legal protection for children and fulfillment of human rights of children, because in principle the accident that befell children general there is certainly a parent's share is not wise in making decisions.The approach used by the author is the normative juridical approach. Normative research is a legal research conducted by examining library materials or secondary. The research conducted by the writer is to analyze how the criminal responsibility done by the parent as a result of the traffic accidents case experienced by the child in Sleman Police area and criminal alternative in order to be able to legal protection for children and the fulfillment of the human rights of the child.The criminal liability of the parent in case of traffic accidents experienced by the Child in the Sleman Police territory in the application can not be done, because based on the elements of criminal offense in the liability process must be done by the person doing the act intentionally or negligence, positively applicable in Indonesia under Article 77 of the Indonesian Criminal Code states that